ALGORITHM AND COMPUTER PROGRAM FOR DETERMINATION OF HIGH PRECISION VALUE OF MEASUREMENT AND METROLOGICAL CONTROL - КОРОГОД, Г. О.; ЯХНО, В. М. (Technologies and Engineering, 2024)
Purpose. Break down the algorithm and the corresponding computer program for determining the high-precision value of the value measured by the sensor with a quadratic transformation function, as well as for metrological control of the current values f the sensor parameters. Methodology. For the correct representation of the signal conversion process in the sensor and error estimation, the methods of redundant measurements of physical quantities, analytical methods of analysis, and methods of mathematical modeling were applied. The method of partial goals was used in the construction of the algorithm. When programming, a static method (class method) was used. Findings. The proposed algorithm and the computer program developed on its basis allow: 1) to determine a high-precision value of the desired physical quantity, which does not depend on changes in the parameters of the transformation function (per measurement cycle); 2) determine the current values of the parameters of the unstable transformation function; 3) establish the presence of deviations of the parameters of the sensor conversion function from their normalized values with a given error. Scientific novelty. The developed algorithm of redundant measurements with a quadratic sensor transformation function and its computer implementation simulate a measurement experiment with the possibility of metrological control of the sensor. Practical value. The developed algorithm and computer program make it possible to obtain a highly accurate value of the desired physical quantity with a nonlinear transformation function without additional steps to linearize it. In addition, the obtained value of the desired quantity, which does not depend on changes in the parameters of the quadratic transformation function of the sensor, makes it possible to apply this approach to inexpensive sensors. Also, it becomes possible to determine the metrological reliability of the sensor with specified parameter deviations, which ensures direct metrological control of the sensor without additional measures for its verification.